Dimitrios Yatromanolakis (ed.). Epigraphy of Art: Ancient Greek Vase-Inscriptions and Vase-Paintings. - Osborne, Robin (Journal of Greek Archaeology, 2018)
The preface of this collection of papers sets out its aim as ‘foregrounding the urgency of establishing a thorough and epigraphically accurate database of ancient Greek vase-inscriptions’ (p.xi), and proceeds, after some general remarks about what gets inscribed, to the cautionary tale of the pyxis in the Metropolitan Museum on which the label for one of the figures, which reads ευνομια, had been misread απονια.